Assessment of the carcinogenic potential of particulate matter generated from 3D printing devices in Balb/c 3T3-1-1 cells - CheolHong Lim; DongSeok Seo (Scientific Reports)
Abstract Recently, there have been reports of sarcoma occurring in a Korean science teachers who used a 3D printer with acrylonitrile butadiene styrene (ABS) and polylactic acid (PLA) filaments for educational purposes. However, limited toxicological research data on 3D printing make it challenging to confirm a causal relationship between 3D printing and cancer. Therefore, occupational accidents involving teachers who have developed sarcoma have not been officially recognized. To address this gap, we aimed to evaluate the carcinogenic potential of particulate matter produced from ABS and PLA filaments commonly used in 3D printing. We created a generator mimicking 3D printing to generate particulate matter, which was used as an experimental material. The collected particulate matter was exposed to an in vitro system to investigate genetic damage, effects on cell transformation, and changes in carcinogenesis-related genes. Various assays, such as the comet assay, cell transformation assays, microarray analysis, and glucose consumption measurement, were employed. Cytotoxicity tests performed to determine the exposure concentration for the comet assay showed that cell viability was 83.6, 62.6, 42.0, and 10.2% for ABS at exposure concentrations of 50, 100, 200, and 400 µg/mL, respectively. PLA showed 91.7, 80.3, 65.1, and 60.8% viability at exposure concentrations of 50, 100, 200, and 400 µg/mL, respectively. Therefore, 50 µg/mL was set as the highest concentration for both ABS and PLA, and 25 and 12.5 µg/mL were set as the medium and low concentrations, respectively. The comet assay showed no changes in genetic damage caused by the particulate matter. Cytotoxicity results performed to establish exposure concentrations in the transformation assay showed that ABS showed cell viability of 88.0, 77.4, 84.7, and 85.5% at concentrations of 1.25, 2.5, 5, and 10 µg/mL, respectively, but few cells survived at concentrations above 20 µg/mL. PLA showed minimal cytotoxicity up to a concentration of 20 µg/ml. Therefore, in the cell transformation assay, a concentration of 10 µg/mL for ABS and 20 µg/mL for PLA was set as the highest exposure concentration, followed by medium and low exposure concentrations with a common ratio of 2. In cell transformation assays, only one transformed focus each was observed for both ABS and PLA particulate matter-exposed cells. The microarray assay revealed changes in gene expression, with a 41.7% change at 10 µg/mL for ABS and an 18.6% change at 20 µg/mL for PLA compared to the positive control group. Analysis of carcinogenesis-related gene expression changes on days 1, 7, and 25 of the promotion phase revealed that in cells exposed to 5 µg/mL of ABS, RBM3 gene expression increased by 3.66, 3.26, and 3.74 times, respectively, while MPP6 gene expression decreased by 0.33, 0.28, and 0.38 times, respectively, compared to the negative control group. Additionally, the measurement of glucose consumption showed that it increased in cells exposed to ABS and PLA particulate matter. Our findings suggest that the carcinogenic potential of ABS- and PLA-derived particulate matter in 3D printing cannot be completely ruled out. Therefore, further research in other test systems and analysis of additional parameters related to carcinogenesis, are deemed necessary to evaluate the carcinogenic risk of 3D printers using these materials.